“I Don’t Know Whom to Trust”: A Quantitative Study of Cybersecurity Awareness, Stress, and the Digital Divide Among Older Adults in India - Priyanacy Gupta (Transactions on Informatics and Data Science, 2026)
This study investigates cybersecurity awareness and perceptions among older adults in Indore, India, focusing on psychological aspects, behavioural factors, and levels of knowledge regarding data protection. The rapid proliferation of Information Technology has not been matched by adequate digital literacy among seniors, leaving them vulnerable to online threats such as financial scams and identity theft. Using a quantitative approach, a structured questionnaire was administered to 115 elderly respondents selected through purposive sampling: 44% aged 50–60, 43% aged 60–70, and 13% aged 70+. 56% of respondents resided in rural areas. Data were analysed using SPSS, employing correlation, regression, and ANOVA. The findings reveal that a lack of technological knowledge significantly contributes to stress (B = 0.430, p < 0.001) and reduces quality of life (B = 0.418, p < 0.001). Behaviours such as trusting anonymous callers and sharing financial information were associated with low data privacy awareness. Correlation analysis indicated a strong negative association between increased knowledge of data protection and concerns about password security (r = –0.625, p < 0.001). The study concludes that significant knowledge gaps heighten older adults’ vulnerability to cyber threats, adversely affecting their psychological well-being and online behaviour. Future research should expand to more diverse and representative samples and evaluate the effectiveness of targeted cybersecurity training programmes. Policy implications include developing senior-friendly technology standards, community-based digital literacy initiatives, and stronger regulatory frameworks for data privacy to foster a safer digital environment for India’s ageing population